Dampak Insentif, Desentraliasi dan Sistim Pengendalian Internal Terhadap Kinerja Pegawai - Gilbert Alvin Rumalatu; Anthoneta Telsy Waelauruw (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2021)
This study aims to test and analyze impact of incentive, decentralization effect and intern government control system to employee performance in Dinas Pariwisata, Pemuda dan Olah Raga Kabupaten Maluku Tengah. Population from the research is from all employees In Dinas Pariwisata, Pemuda dan Olah Raga Kabupaten Maluku Tengah. It takes 46 respondent from the government employees and salaries employees. Data collection is done with a direct survey with census method as a sample gathering method. Hypothesis testing empirically using a Multiple Liniear Regression. The research result shows that incentive is proven positive and significant effect employee performance. This mean if the incentive is raise or getting better have a good effect to employee performances. Decentralization is proven positive and significant to employee performance and this mean that authority delegation and the responsible are not did not go well on employee performance. Further intern control is proven positive and significant effect to employee performance. Which it’s mean if the government control system runs well then it will effect indirectly to employee performance goes better.